Respuesta :

Space

Answer:

[tex]4x[/tex]

Step-by-step explanation:

Step 1: Define

I will substitute delta x with h

[tex]\lim_{h \to 0} \frac{2(x+h)^2-2x^2}{h}[/tex]

Step 2: Simplify function

  1. Expand: [tex]\lim_{h \to 0} \frac{2(x^2+2hx+h^2)-2x^2}{h}[/tex]
  2. Distribute 2: [tex]\lim_{h \to 0} \frac{2x^2+4hx+2h^2-2x^2}{h}[/tex]
  3. Combine like terms: [tex]\lim_{h \to 0} \frac{4hx+2h^2}{h}[/tex]
  4. Factor: [tex]\lim_{h \to 0} \frac{h(4x+2h)}{h}[/tex]
  5. Simplify: [tex]\lim_{h \to 0} 4x+2h[/tex]

Step 3: Evaluate limit

[tex]\lim_{h \to 0} 4x+2h=\lim_{h \to 0} 4x+2(0)[/tex]

[tex]\lim_{h \to 0} 4x+2(0)=\lim_{h \to 0} 4x+0[/tex]

[tex]\lim_{h \to 0} 4x+0 = 4x[/tex]